PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN FASILITAS KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA LPD DI KECAMATAN BULELENG - Komang Trisna Sari Dewi; Gede Supartawan (Jurnal Riset Entrepreneurship, 2023)
The reason for this study was to determine the effect of organizational culture, organizational commitment and work facilities on job satisfaction at LPD in Buleleng District. The research method uses validity, reliability, classical assumptions, multiple linear regression, t-test, determination and f-test tests. The results showed that organizational culture affects LPD job satisfaction in Buleleng District. The results of the study that organizational culture affects job satisfaction. Organizational commitment is very influential on the job satisfaction of LPD in Buleleng District. From the test results that organizational commitment affects job satisfaction. Work facilities affect LPD job satisfaction in Buleleng District. The results of the study found that work facilities had a significant effect on job satisfaction. Simultaneous test results show F-count > F-table, (246.628 > 3.11), this indicates that organizational culture factors, organizational commitment and work facilities influence job satisfaction with sig. 0.000 < 0.050.